2016
DOI: 10.26719/2016.22.12.860
|View full text |Cite
|
Sign up to set email alerts
|

Childhood recurrent abdominal pain and Helicobacter pylori infection, Islamic Republic of Iran

Abstract: We examined the role of Helicobacter pylori infection as a cause of recurrent abdominal pain (RAP) among Iranian children in a population-based case-control study to determine the association between H. pylori infection and RAP among schoolchildren. A total of 1558 children aged 6-13 years were examined. Children with RAP confirmed by the Apley and Naish criteria were selected; 145 cases were selected for inclusion and were compared with 145 healthy children recruited from the same area. Both groups underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 9 publications
2
16
1
1
Order By: Relevance
“…7 Alimohammadi et al in Iran also found gender did not have a statistical difference (p=0.8). 17 Our study found girls more dominant in the two groups: 71.1% in group 1 and 61.5% in group 2, but there is no significant difference between the two groups with p = 0.353. Hagag et al in Egypt found the mean age of H. pylori infection 8.5 ± 1.65 years, and there is no significant difference between age and H. pylori infection with p = 0.743.…”
Section: Discussioncontrasting
confidence: 58%
“…7 Alimohammadi et al in Iran also found gender did not have a statistical difference (p=0.8). 17 Our study found girls more dominant in the two groups: 71.1% in group 1 and 61.5% in group 2, but there is no significant difference between the two groups with p = 0.353. Hagag et al in Egypt found the mean age of H. pylori infection 8.5 ± 1.65 years, and there is no significant difference between age and H. pylori infection with p = 0.743.…”
Section: Discussioncontrasting
confidence: 58%
“…Children with RAP had a higher H. pylori infection rate than the control group (58.6% vs 44.8%), but there was no significant difference between the RAP symptoms in H. pylori ‐positive children vs H. pylori ‐negative ones . A prospective observational study analyzed 240 Brazilian children and adolescents, mean age 9.8 years (range 4‐17) with chronic nonulcer dyspepsia, who underwent upper gastrointestinal endoscopy with biopsies. H. pylori infection was identified in 52% of cases.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Clinical manifestation related to the gastrointestinal tract commonly consist of nocturnal pain, abdominal pain in the epigastric region that relief with antacid treatment, and acute or chronic gastrointestinal bleeding (hematemesis, hematochezia, or melena). 16,17 Clinical manifestation H. pylori infection non-gastrointestinal tract, especially iron-deficiency anemia, idiopathic thrombocytopenia purpura (ITP), vitamin B12 deficiency, and allergies. 18 A systematic review and meta-analysis by Muhsen et al in 2008 found H. pylori is the main factor causing iron deficiency anemia.…”
Section: Discussionmentioning
confidence: 99%